The effect of climate on leaf micromorphological characteristics in some broad-leaved species - Sevik, Hakan; Cetin, Mehmet; Ozel, Halil Baris; Erbek, Abdullah; Zeren Cetin, Ilknur (Springer Science and Business Media LLC, 2020)
This study aimed to determine the change in micromorphological characteristics depending on the species and the climate conditions in some landscape plants grown in areas with different climate conditions. For this purpose, leaf samples of five different woody species from the areas dominated by continental, Black Sea and Mediterranean climates were collected, and the scaled images of these samples were obtained via scanning electron. The stoma length, stoma width, pore length, pore width and stoma density were determined using the measurements conducted on these scaled images. The obtained data were evaluated statistically, and changes in these characteristics depending on the climate and the species were determined. The lowest values for all characteristics, except stoma density, were obtained in the terrestrial climate, whereas the highest values were obtained in plants grown in the Mediterranean climate. In terms of stoma density, the lowest value was obtained in plants grown in the Mediterranean climate, whereas the highest values were obtained in terms of other characteristics, and the highest value was obtained in plants grown in the terrestrial climate, whereas the lowest values were obtained in terms of other characteristics. However, when the changes depending on the species were examined, it was determined that different species react differently depending on the climate type.
Keywords: Climate; Sem; Management, Monitoring, Policy and Law; Micromorphological Characteristics; Stoma; 15. Life on land